Perceptions about Probiotic Yogurt for Health and Nutrition in the Context of HIV/AIDS in Mwanza, Tanzania (Journal of Health, Population and Nutrition, 2012)
Recently, the food and malnutrition issues have taken centre stage within the arena of HIV/AIDS epidemic, with several calls being made for context-specific health and nutrition interventions to deal with   the emerging food insecurity and malnutrition issues in settings with high burdens of HIV/AIDS. The use of probiotics as nutritional supplements in HIV/AIDS-affected and resource-poor settings has also been advocated. This paper presents the results of a qualitative study on community knowledge and perceptions about probiotics and their potential impact on peoples everyday life in the context of the HIV/AIDS epidemic. In-depth interviews (n=26) were conducted with residents in Mwanza, Tanzania. The results showed that people living with HIV/AIDS, who were using probiotic yogurt produced through a joint partnership of Western Heads East, Tanzania Medical Research Institute and the Tukwamune Womens  Group, reported perceived beneficial effects, such as gain in weight and improved health and well-being.  Yet, these beneficial effects might be resulting in growing misconceptions about probiotic yogurt being  medicine for the treatment of HIV/AIDS; this is leading some people living with HIV/AIDS to abandon  taking their antiretroviral medications based on the view that the probiotic yogurt is making them feel much better. The findings illustrate the potential challenges with regard to the introduction of nutritional food supplements into new contexts plagued by malnutrition and infectious diseases. Public-health education   and awareness programmes are needed when introducing novel foods into such contexts.   DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11273   J HEALTH POPUL NUTR 2012 Mar;30(1):31-40